Study on physical, electrical, magnetic and energy harvesting performances of eco-friendly piezoelectric ceramics (1 − x)[0.995BNKT–0.005LN]–xFe2O3 complex system - Pimpilai Wannasut; Orawan Khamman; Pharatree Jaita; Methee Promsawat; Jira Patthanavarit; Anucha Watcharapasorn (Journal of Asian Ceramic Societies)
In this work, the complex lead-free piezoelectric ceramics with formula (1 − x)[0.995 Bi0.5(Na0.80K0.20)0.5TiO3–0.005LiNbO3]–xFe2O3, where x = 0, 0.010, 0.015 and 0.020 mol fraction, have been prepared via a conventional solid-state method. The effects of Fe2O3 doping on the physical, microstructural electrical, energy harvesting and magnetic properties have been systematically investigated. All ceramics were sintered at 1150°C for 2 hours with obtained relative density of ~ 96-97%. The XRD and Raman data revealed the coexisting rhombohedral and tetragonal phases for all samples. SEM image presented angular grain packing with the average grain size range of 0.43–1.03 μm. The addition of Fe2O3 content improved in electrical properties of undoped sample particularly at a composition of x = 0.015. The maximum values of εm = 6250, Smax = 0.29, d*33 = 578 pm/V, d33 = 211 pC/N and FOM = 3.54. All ceramics indicated ferromagnetic behavior with slim hysteresis shape. The results suggest a potential for its applications as an eco-friendly compound for further use in sensor, spintronic and microelectronic devices applications.